Modified Proportional Resonant Current Controller with MPPT for Three Phase Single Stage Grid Integrated PV System - Mishra M.K.; Lal V.N. (My University, 2025)
This paper proposes a modified proportional-Resonant (MPR) current controller with dc-link voltage controller and maximum power point tracking (MPPT) controller for a three-phase grid-integrated photovoltaic (GIPV) system. The proposed PR controller supports the GIPV system to inject grid current with low total harmonic distortion (THD) during distorted grid voltage conditions. The complete control strategy uses α-β reference frame for MPR controller with harmonic compensator and interlinked with d-q reference frame-based voltage controller. A modified INC algorithm is used with MPR, which provides faster tracking with steady-state low power oscillations in the presence of distorted grid voltage. The proposed current harmonics reduction scheme is verified by using software-in-the-loop (SIL) environment of the OPAL-RT OP4510. The effectiveness of the proposed MPR current controller is validated through OPAL-RT results are compared to the conventional proportional-integral (PI) and the conventional PR controller. © 2020 IEEE.